The Influence Of Corporate Governance On Integrated Reporting Disclosure Moderated By Type Auditor - Hasnaul Afifah (Syntax Corporation Indonesia, 2022)
The objective of this research is to the influence of independent board members, board size, female board, type of auditor to independent board members as a moderating variable on IRD The sample in this study was the LQ45 Non-Banking on Indonesia Stock Exchange in 2016-2020 period with a purposive sampling technique. The analytical tool used was Eviews 10 (x64). The result is independent board members have a positive effect and negative significant on IRD, board size have a positive effect on IRD, female board have a no effect on IRD, and type of auditor no strengthens independent board members on IRD